2017
DOI: 10.1109/tnsre.2016.2554061
|View full text |Cite
|
Sign up to set email alerts
|

An Empirical Evaluation of Force Feedback in Body-Powered Prostheses

Abstract: Myoelectric prostheses have many advantages over body-powered prostheses, yet the absence of sensory feedback in myoelectric devices is one reason body-powered devices are often preferred by amputees. While considerable progress has been made in the mechanical design and control of myoelectric prostheses, research on haptic feedback has not had a similar impact. In this study, we seek to develop a fundamental understanding of the utility of force feedback and vision in the functional operation of a body-powere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 23 publications
3
17
0
Order By: Relevance
“…Previous literature has shown that myoelectric prostheses may benefit from the addition of haptic feedback [7,18,21]. In this study, we show that task performance is equally improved over no haptic feedback, regardless of the specific haptic feedback modality used.…”
Section: Limitationssupporting
confidence: 52%
See 2 more Smart Citations
“…Previous literature has shown that myoelectric prostheses may benefit from the addition of haptic feedback [7,18,21]. In this study, we show that task performance is equally improved over no haptic feedback, regardless of the specific haptic feedback modality used.…”
Section: Limitationssupporting
confidence: 52%
“…The exoskeleton was capable of de- livering a maximum torque of 3.24 Nm as a flexion moment at the elbow joint. This exoskeleton was originally presented in previous work by members of our research group, Brown et al [7]. An explanation of the joint-torque stimulus is detailed in Section 2.6.4.…”
Section: Experimental Apparatusmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the list of known issues relating to current myoelectric arms, remains long. It contains electrode related skin rashes [ 98 , 99 ], sweat interference with electrode functioning [ 84 ], postural interference [ 140 ], high weight and distal center of gravity, insufficient durability [ 47 ], noisy distraction [ 141 ], absent proprioceptive feedback [ 142 ], uncoordinated grips [ 93 ], fragile prosthetic gloves [ 143 ], extreme costs [ 144 ] and unattractive appearance [ 45 , 145 ].…”
Section: Discussionmentioning
confidence: 99%
“…For individuals with transradial limb loss, body-powered devices are typically controlled by a figure-of-nine harness through movement of the contralateral shoulder [ 1 ]. This type of control allows easy activation and provides a measure of sensory feedback of aperture and grip force [ 8 ]; however, it can also cause shoulder pain or injury and motivate device abandonment [ 1 ]. Although these devices are quite different from their myoelectric counterparts, their rejection rate is quite similar (26%) [ 4 ], and while myoelectric and body-powered prostheses each exhibit specific strengths and weaknesses, neither provide an overall advantage over the other [ 9 ].…”
Section: Introductionmentioning
confidence: 99%